Tuning optical absorption in perovskite (K,Na)NbO3 ferroelectrics - Vetokhina, V; Nepomniashchaia, N; de Prado, E; Pacherova, O; Kocourek, T; Anandakrishnan, S S; Bai, Y; Dejneka, A; Tyunina, M (Materials advances, 2024)
The ability to tailor the electronic band structure and optical absorption by appropriate cationic substitution in perovskite oxide ferroelectrics is essential for many advanced electronic and optoelectronic applications of these materials. Here, we explored weak (Ba,Ni)-doping for reducing optical bandgaps in (K,Na)NbO3 ferroelectric films and ceramics. The optical absorption in the broad spectral range of (0.7-8.8) eV was investigated in polycrystalline doped, pure, and oxygen deficient films, in doped epitaxial films grown on different substrates, and in doped ceramics. By comparing optical properties of all films and ceramics, it was established that 1-2 at% of cationic substitutions or up to 10 at % of oxygen vacancies have no detectable effect on the direct (∼4.5 eV) and indirect (∼3.9 eV) gaps. Concurrently, substantial sub-gap absorption was revealed and ascribed to structural band tailing in epitaxial films and ceramics. It was suggested that owing to fundamental strain-property couplings in perovskite oxide ferroelectrics, inhomogeneities of lattice strain can lead to increased sub-gap absorption. The uncovered structurally induced sub-gap optical absorption can be relevant for other ferroelectric ceramics and thin films as well as for related perovskite oxides.